A lead–porphyrin metal–organic framework: gas adsorption properties and electrocatalytic activity for water oxidation. Issue 1 (25th November 2015) - Dai, Fangna; Fan, Weidong; Bi, Jiahui; Jiang, Peng; Liu, Dandan; Zhang, Xirui; Lin, Huan; Gong, Chuanfang; Wang, Rongming; Zhang, Liangliang; Sun, Daofeng
Abstract : A 3D non-interpenetrating porous metal–organic framework shows electrocatalytic activity for water oxidation in alkaline solution. Abstract : A 3D non-interpenetrating porous metal–organic framework [Pb2 (H2 TCPP)]·4DMF·H2 O (Pb-TCPP) (H6 TCPP = 5, 10, 15, 20-tetra(carboxyphenyl)porphyrin) was synthesized by employment of a robust porphyrin ligand. Pb-TCPP exhibits a one-dimensional channel possessing fairly good capability of gas sorption for N2, H2, Ar, and CO2 gases, and also features selectivity for CO2 over CH4 at 298 K. Furthermore, Pb-TCPP shows electrocatalytic activity for water oxidation in alkaline solution. It is the first 3D porous Pb-MOF that exhibits both gas adsorption properties and electrocatalytic activity for an oxygen evolution reaction (OER).